Relatório de Estágio Profissional "Do outro lado da aprendizagem: Um sonho que quero voltar a viver" - Pedro Nuno Martins Cordeiro (2019)
This document exposes the trajectory of a student-intern (author) in Professional Internship, which provided the creation of a unique professional identity as a future Physical Education teacher. Teaching practice, other experiences in the school context and all critical reflections were essential to the construction of this identity. The pedagogical practices took place at the Escola Secundária do Castêlo da Maia, in an internship nucleus composed by several elements, three young students, with unique characteristics and personalities, led by an available and responsible teacher (cooperating teacher), and by a faculty advisor. This document makes possible to understand the author's path during this long year, and the different situations he lived, faced and resolved. It is organized in six chapters: Introduction, where the proposit of this document is exposed, Biographical Context, in which the personal aspects is highlighted and some details about the author are revealed; Professional Practice Framework, where it is explained the context of the internship; Professional Practice Operationalization, where we have the Teaching and Learning Organization and Management, School Participation and Community Relations, Professional Development where is the research study; Conclusions and Future Perspectives, where is a reflection, in a personal perspective, of the importance of the professional internship; Bibliographic References; Attachments. The biggest and most valuable learnings that the intern student had during this school year were linked to the teaching-learning process of the resident class and to the daily interaction with his interns and cooperating teacher. It was a year or personal fulfillment, full of learnings, a dream come true, being a teacher.